Bible animals - Beets, Sally (London DK Publishing, 2018)
A Bible-themed board book introduces engaging animals from the Bible, including a woolly lamb, a smooth whale, and a soft dove
Picture Book
27
Keywords: Animals in the Bible -- Juvenile literature; Board books; Textured books -- Specimens